English Needs Analysis for Technology Students at A Technopreneurship-based University - Eka Grana Aristyana Dewi; A.A. Gede Adi Mega Putra (Universitas Sulawesi Barat, 2026)
In the context of rapid digital transformation, English proficiency has become a strategic competency for students in technopreneurship-oriented information technology programs. However, discrepancies remain between students’ current competence and the communicative demands of startup ecosystems. This study aims to identify the specific English language needs of technopreneurship-based IT students using Dudley-Evans and St. John’s (1998) Needs Analysis framework. A descriptive mixed-method design was employed, involving 38 respondents (students, alumni, and industry practitioners). The questionnaire demonstrated strong content validity (S-CVI/Ave=0.98) and acceptable internal consistency across core dimensions. Quantitative findings indicate a substantial gap between Target Situation demands (M=9.16) and Present Situation competence (M=5.08), confirming substantial professional communication “lacks.” Qualitative thematic analysis using NVivo further highlights the prioritization of productive skills, particularly digital content writing and professional complaint handling, as key industry necessities. By systematically mapping findings into the domains of necessities, lacks, and wants, this study contributes to contemporary ESP discussions in digitally mediated and entrepreneurial contexts. The study recommends a hybrid pedagogical model integrating task-based learning and communicative language teaching to enhance authentic task performance and sociolinguistic competence in technology-driven higher education.